Knowledge, Attitude, and Practice of Hand Hygiene among Medical student and Nurses at a Tertiary Health Care Centre in Ratlam, Madhya Pradesh - Prafulla Songara; Gaurav Saxena (Tropical Journal of Pathology and Microbiology, 2021)
Background: Hand hygiene is considered as the leading measure to prevent cross-transmission of microorganisms. Regarding hospital acquired infections, the compliance with hand washing guidelines seems to be vital in preventing the disease transmission among patients. The objective of this study was to assess level of knowledge, attitude and practice in various aspects of hand hygiene in medical students and nurses for identifying gaps in hospital infection control adherence and planning necessary corrective measures. Methods : A cross-sectional study was conducted among 70 medical student and 50 nurses in a tertiary medical college in India. Knowledge was assessed using WHO hand hygiene questionnaire. Attitude and practices were evaluated by using another self-structured questionnaire. Results: Both the study groups exhibited moderate levels of knowledge regarding hand hygiene. Nurses were found to exhibit a higher level of attitude and practice than medical students. Conclusions: Present study highlights the need of periodical training sessions regarding hand hygiene practices among the health care workers to provide the current knowledge in the area with a behavioral change in attitudes and practices leading to reduction of nosocomial infections.